Effect of fisheries subsidies negotiations on fish production and interest rate - Radika Devi Kumar; Ronald Ravinesh Kumar; Peter Stauvermann; Pallavi Arora (Journal of Risk and Financial Management, 2020)
We analyze the effect of fisheries subsidy negotiations on financial markets and aggregate demand in developed and developing countries. We examine the plausible scenarios that are likely to emerge in the event of elimination or reduction of subsidies, and the subsequent effect on the financial markets and the fish production. We use the Keynesian macroeconomic static framework, which is based on an extended well-known investment-savings (IS) and liquidity preference-money supply (LM) model for analysis. Our analysis shows that the impact of a reduction in fisheries subsidies would reduce the exploitation of fish and marine resources in developing countries, thus leading to a general increase in fish prices and quantity stabilizing at lower levels. We also find that this effect would transfer to financial markets, leading to a decline in interest rates for fish exporting developing countries, but interest rates tend to stabilize at higher levels for fish importing developed countries.
Keywords: 330; fisheries subsidies; financial markets; interest rates; international trade